Medical students' empathy positively predicts charitable donation behavior. Issue 6 (1st November 2020) - Smith, Karen E.; Norman, Greg J.; Decety, Jean
ABSTRACT: Empathy is known to motivate prosocial behavior. This relationship, however, is complex and influenced by the social context and the type of prosocial behavior. Additionally, empathy is a complex psychological capacity, making it important to examine how different components influence different prosocial behaviors. The current study uses a unique longitudinal sample to assess how changes in cognitive and affective components of empathy relate to charitable giving. Measures of empathy were collected from medical students in the fall and spring of students' first three years of medical school. After this time, students had the opportunity to donate to charity. Positive changes in students' cognitive empathy predicted their charitable giving, with students who demonstrated greater increases in cognitive empathy giving more money. This study points to an important role for cognitive empathy in generosity, and suggests that long-term changes in empathy influence individual differences in prosocial behavior. Abbreviations: Questionnaire of Cognitive and Affective Empathy (QCAE); Jefferson Scale of Physician Empathy - Student Version (JSE); Variance Inflation Factor (VIF)